Survivors of Slavery : Modern-Day Slave Narratives. - Murphy, Laura (Columbia University Press, 2014)
Slavery is not a crime confined to the far reaches of history. It is an injustice that continues to entrap twenty-seven million people across the globe. Laura Murphy offers close to forty survivor narratives from Cambodia, Ghana, Lebanon, Macedonia, Mexico, Russia, Thailand, Ukraine, and the United States, detailing the horrors of a system that forces people to work without pay and against their will, under the threat of violence, with little or no means of escape. Representing a variety of circumstances in diverse contexts, these survivors are the Frederick Douglasses, Sojourner Truths.